The continuing training of higher education professors and its relationship with the National Curriculum Guidelines - Maria Isabel Lopes; Tiago Weizenmann (Revista Brasileira de Ensino Superior, 2019)
This study is the result of a research carried out by the Pedagogical Support Nucleus, with the professors of the University of Vale do Taquari - Univates, about the contributions promoted by the activities of continuing formation that are part of the institutional program for teacher qualification. The purpose of this article is to analyze, from a cutout in the data from the research, the discourses of university professors on the relationship between continuing formation in Higher Education and the National Curricular Guidelines. As methodological procedures applied to the study, we considered normative documents that retrieve the history of the Curricular Guidelines in Brazil, and the information collected through a questionnaire with structured, objective and open questions, answered voluntarily and anonymously. For the treatment of the data, we proceeded from approximations to the studies of Michel Foucault, considering the construction of discourses that express the contemporary possibilities for the university pedagogy. In this sense, it is possible to identify that professors have constructed, from the participation in forums of the institutional program of teacher qualification, new subjectivities for the profession, materialized in the discourses that evince the appropriation of principles and elements of the National Curricular Guidelines, such as flexibility, autonomy, skills, competences, social demands, articulation between theory and practice, and differentiated teaching methodologies.